Comparing the Effect of Aquatic-Based Exercise vs. Land-Based Exercise on Functional Movement and Physical Performance in Down Syndrome Youth: Experimental Study - Al Zayat, Ahlam; Gaith Abdulbaset (AlQalam Journal of Medical and Applied Sciences, 2025)
Down syndrome, frequently abbreviated as DS, is a chromosomal disorder whereby a baby is born with an additional copy of chromosome 21. Down syndrome youth have been found to present with a limitation of balance, coordination, as well as the loss of gross motor and fine motor skills. This study aimed to establish the difference between the impact of aquatic-based exercises versus exercises performed on land on practical exercises involving functional movements and physical performance among Libyan young with Down Syndrome. The study involved 14 intellectually disabled individuals from two care centers in Tripoli, Libya. They were equally divided into 2 groups. All patients followed the physiotherapy program based on exercise and aquatic therapy for 1 hour, 3 times a week for 1 month. For the exercise intervention, the subjects were advised not to engage in the rest forms of exercise training. For all participants’ functional fitness capacity, pre-tests were performed before the start of the intervention. The measures of functional fitness capacity were: body composition, weight and height, gait speed test, 10-meter walk test, balance test, single leg stance -eye opened/closed, muscle endurance of the upper body muscles, 1-minute push-ups, physical performance, and aerobic capacity; 100-meter timed test. All received data were processed statistically with Microsoft Excel (2020); p-values of various tests were used to determine the statistical significance (e.g., balance, coordination, lung capacity), to find out the differences in performance before and after the training. The level of significance was set at 0.05. data showed that the aqua therapy provided good improvement on the muscles related to gait speed(P=0.00004), muscle endurance(P=0.004) and aerobic capacity(P=0.00000186), a significant difference was observed for single leg stance test with eye closed (P= 0.0001) eye opened (P= 0.0003) in Favor to Land based exercise group. The study concluded that Aquatic-based exercise has a clear effect on physical performance and functional movement in youth with Down syndrome. متلازمة داون هي اضطراب كروموسومي يولد فيه الطفل بنسخة إضافية من الكروموسوم 21. وقد وجد أن الشباب المصابين بمتلازمة داون يعانون من قيود في التوازن والتنسيق بالإضافة إلى فقدان المهارات الحركية الإجمالية والمهارات الحركية الدقيقة. وكان الهدف من هذه الدراسة هو تحديد الفرق بين تأثير التمارين المائية مقابل التمارين التي يتم إجراؤها على الأرض على التمارين العملية التي تنطوي على حركات وظيفية وأداء بدني بين الشباب الليبيين المصابين بمتلازمة داون. شملت الدراسة 14 فردًا من ذوي الإعاقة الفكرية من مركزين للرعاية في طرابلس ليبيا. تم تقسيمهم بالتساوي إلى مجموعتين. اتبع جميع المرضى برنامج العلاج الطبيعي القائم على التمارين والعلاج المائي لمدة ساعة واحدة، 3 مرات في الأسبوع لمدة شهر. لغرض تدخل التمارين، نُصح الأشخاص بعدم الانخراط في أشكال الراحة من تدريب التمارين. تم إجراء اختبارات مسبقة لقدرة اللياقة البدنية الوظيفية لجميع المشاركين قبل بدء التدخل. كانت مقاييس قدرة اللياقة البدنية الوظيفية هي؛ تكوين الجسم؛ الوزن والطول، اختبار سرعة المشي؛ اختبار المشي لمسافة 10 أمتار، اختبار التوازن؛ وضعية الساق الواحدة - العين مفتوحة / مغلقة، قدرة التحمل العضلية لعضلات الجزء العلوي من الجسم؛ تمرين الضغط لمدة دقيقة واحدة، الأداء البدني والقدرة الهوائية؛ اختبار 100 متر محدد الوقت. تمت معالجة جميع البيانات المستلمة إحصائيًا باستخدام Microsoft Excel (2020)؛ تم استخدام القيم الاحتمالية للاختبارات المختلفة لتحديد الأهمية الإحصائية (على سبيل المثال، التوازن والتنسيق وسعة الرئة)، لمعرفة الاختلافات في الأداء قبل التدريب وبعده. تم ضبط مستوى الأهمية عند 0.05. أظهرت البيانات أن العلاج المائي قدم تحسنًا جيدًا في العضلات المتعلقة بسرعة المشي (P = 0.00004) وتحمل العضلات (P = 0.004) والقدرة الهوائية (P = 0.00000186)، لوحظ فرق كبير في اختبار وضعية الساق الواحدة مع إغلاق العين (P = 0.0001) وفتح العين (P = 0.0003) لصالح مجموعة التمارين القائمة على الأرض. وخلصت الدراسة إلى أن التمارين الرياضية المائية لها تأثير واضح على الأداء البدني والحركة الوظيفية لدى الشباب المصابين بمتلازمة داون